A geomorfologia perante a ciência geográfica: algumas reflexões / Geomorphology in geographical science: some reflections - Antonio de Sousa Pedrosa (Sociedade & Natureza)
The first aim of Geography is to explore and explain the geographic space. Modern science requires a theoretical rather than an obsession with classification, ie, there is a need for epistemological models that defines the theoretical objects, work with concepts and establish laws. In order to understand the current position of the geographer and more specifically the physical geographer, it is important to understand, how is the evolution of this science and what the fundamental concepts by which it falls. In this paper we discuss some problems inherent in their epistemological status intend to contribute to the understanding of some concepts and changing trends, which are the basis of geographical science and more specifically of Physical Geography. The aim is also to emphasize the importance of geomorphology in the basic training of a geographer, and intended to provoke reflection and at the same time, raise an awareness of the relationship that exists between the fundamental theoretical and practical activity of the future geographers.